Random-walk model to study cycles emerging from the exploration-exploitation trade-off - Kazimierski, Laila Daniela (2015)
Fil: Kazimierski, Laila Daniela. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina